A Tandem Repeat in Decay Accelerating Factor 1 Is Associated with Severity of Murine Mercury-Induced Autoimmunity. (10th April 2014) - Cauvi, David M.; Gabriel, Rodney; Kono, Dwight H.; Hultman, Per; Pollard, K. Michael
Abstract : Decay accelerating factor (DAF), a complement-regulatory protein, protects cells from bystander complement-mediated lysis and negatively regulates T cells. Reduced expression of DAF occurs in several systemic autoimmune diseases including systemic lupus erythematosus, and DAF deficiency exacerbates disease in several autoimmune models, including murine mercury-induced autoimmunity (mHgIA). Daf1, located within Hmr1, a chromosome 1 locus associated in DBA/2 mice with resistance to mHgIA, could be a candidate. Here we show that reduced Daf1 transcription in lupus-prone mice was not associated with a reduction in the Daf1 transcription factor SP1. Studies of NZB mice congenic for the mHgIA-resistant DBA/2 Hmr1 locus suggested that Daf1 expression was controlled by the host genome and not the Hmr1 locus. A unique pentanucleotide repeat variant in the second intron of Daf1 in DBA/2 mice was identified and shown in F2 intercrosses to be associated with less severe disease; however, analysis of Hmr1 congenics indicated that this most likely reflected the presence of autoimmunity-predisposing genetic variants within the Hmr1 locus or that Daf1 expression is mediated by the tandem repeat in epistasis with other genetic variants present in autoimmune-prone mice. These studies argue that the effect of DAF on autoimmunity is complex and may require multiple genetic elements.